Phytoplankton in Eutrophic Waters of Hurun Bay: An Examination of Composition Patterns, Structure, and Impacts on Aquatic Ecosystems - Maestro Munru; Meutia Samira Ismet; yoman Metta N Natih; Beginer Subhan; Nasrul Aziz (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Ecological conditions are shifting due to increased anthropogenic activities along coastal areas. These activities are affecting the life cycle of aquatic organisms, especially phytoplankton. This study, conducted in the unique ecosystem of Hurun Bay Lampung, aims to analyze the composition and structure of phytoplankton communities in eutrophic waters and water quality conditions. Sampling was conducted in two different months, August and October, by vertical hauling from a depth of 5 meters to the surface. The results revealed a rich diversity of phytoplankton, with 72 genera, 48 families, and 6 classes identified in August, and 55 genera, 42 families, and 6 classes identified in October. The diatom group was the most prevalent, accounting for over 90% of the total, with the highest abundance found in Skeletonema and Chaetoceros. The diversity, uniformity, and dominance indices were all in the low to medium category, indicating a balanced ecosystem.